1997
DOI: 10.1093/brain/120.12.2179
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic focal dystonia: a disorder of muscle spindle afferent processing?

Abstract: As muscle spindles are involved in the sensation of position and movement of the body, we tested their involvement in the pathophysiology of idiopathic focal dystonia. Twenty patients with torticollis, nine with writer's cramp, two with blepharospasm and 16 healthy control subjects participated. In the first task, the blindfolded subject matched the position of the passively moved forearm with the opposite forearm when the elbow joint was slowly flexed. In a second matching task, passive movement was replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
109
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 9 publications
13
109
1
2
Order By: Relevance
“…This view suggests that synchronous activation of several digits by vigorous and frequent musical practice leads to a disordered and smeared representation of the fingers in somatosensory and probably also in motor cortex, with the inability to move the most affected fingers separately (2,18). Also, sufficient evidence now exists to demonstrate a corresponding defective perception and abnormal sensory processing in focal hand dystonia (5,(19)(20)(21)(22). Given these abnormalities as well as the difficulties in currently available symptomatic treatments, new sensory and motor training programs have been developed and tested (3,4,23).…”
mentioning
confidence: 99%
“…This view suggests that synchronous activation of several digits by vigorous and frequent musical practice leads to a disordered and smeared representation of the fingers in somatosensory and probably also in motor cortex, with the inability to move the most affected fingers separately (2,18). Also, sufficient evidence now exists to demonstrate a corresponding defective perception and abnormal sensory processing in focal hand dystonia (5,(19)(20)(21)(22). Given these abnormalities as well as the difficulties in currently available symptomatic treatments, new sensory and motor training programs have been developed and tested (3,4,23).…”
mentioning
confidence: 99%
“…Abnormalities in proprioception in distant areas from the neck have been shown (Grünewald et al., 1997; Putzki et al., 2006), whereas research concerning neck proprioception reported contradicting results. Bove et al.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate neck proprioception is important to keep the head upright (Shaikh, Wong, Zee, & Jinnah, 2013; Anastasopoulos et al., 1998) and to maintain posture and balance (Mergner, Nasios, Maurer, & Becker, 2001; Treleaven, 2008). Previous investigation of cervical proprioception in patients with CD shows abnormal perception of movement induced by muscle vibration (Bove, Brichetto, Abbruzzese, Marchese, & Schieppati, 2004; Lekhel et al., 1997; Grünewald, Yoneda, Shipman, & Sagar, 1997), abnormal sensory processing in both somatosensory cortices (Molloy, Carr, Zeuner, Dambrosia, & Hallett, 2003), and impaired reflex–voluntary interactions involving neck proprioceptive reflexes (Anastasopoulos, Maurer, & Mergner, 2014). It is, however, unclear to what extend these laboratory induced alterations in neck proprioception are present during voluntary neck movements and cervical sensorimotor control.…”
Section: Introductionmentioning
confidence: 99%
“…Kinesthesia is also impaired (101)(102)(103) and abnormal somatotopy was demonstrated by somatosensory evoked potential mapping based on EEG (94), MEG (94,104,105) and fMRI (106)(107)(108). As for motor control, a loss of lateral inhibition in sensory processing in space and time was reported (109)(110)(111).…”
Section: Or Cerebellum (93)mentioning
confidence: 99%